2010
DOI: 10.1136/bcr.03.2010.2863
|View full text |Cite
|
Sign up to set email alerts
|

Postpartum ovarian vein thrombosis presenting as ureteral obstruction

Abstract: Ovarian vein thrombosis (OVT) is a relatively uncommon but serious postpartum complication. Although infrequent, OVT may progress to involve the inferior vena cava, the renal vein or may cause sepsis and septic pulmonary embolism, all of which are potentially life-threatening. Clinical misdiagnosis is common, and, unfortunately, most affected women undergo laparotomy for possible appendicitis. We present an interesting case of OVT presenting as ureteral obstruction in a postpartum woman who was in her early 20… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 11 publications
0
6
0
Order By: Relevance
“…Ovarian vein thrombophlebitis (OVT) is a relatively rare disorder associated with multiple pelvic conditions, including recent childbirth, pelvic inflammatory disease, malignancy, chemotherapy, and pelvic surgery (56). Among women of childbearing age, it is more commonly seen in the immediate postpartum period, with a reported incidence ranging from one in 600 to one in 2000 deliveries, and it is much more common after cesarean delivery than after vaginal delivery (56). It is currently thought to arise from bacterial seeding as a result of endometritis, resulting in infectious thrombophlebitis.…”
Section: Ovarian Vein Thrombophlebitismentioning
confidence: 99%
See 1 more Smart Citation
“…Ovarian vein thrombophlebitis (OVT) is a relatively rare disorder associated with multiple pelvic conditions, including recent childbirth, pelvic inflammatory disease, malignancy, chemotherapy, and pelvic surgery (56). Among women of childbearing age, it is more commonly seen in the immediate postpartum period, with a reported incidence ranging from one in 600 to one in 2000 deliveries, and it is much more common after cesarean delivery than after vaginal delivery (56). It is currently thought to arise from bacterial seeding as a result of endometritis, resulting in infectious thrombophlebitis.…”
Section: Ovarian Vein Thrombophlebitismentioning
confidence: 99%
“…This distribution has been ascribed to the more common dextrotorsion of the gravid uterus compressing the right ovarian vein as it crosses the pelvic brim. In addition, the right ovarian vein is longer than the left, with many valves that may contribute to the thrombus formation (56). Moreover, left gonadal vein flow has been shown to be retrograde during pregnancy, preventing upstream bacterial seeding.…”
Section: Ovarian Vein Thrombophlebitismentioning
confidence: 99%
“…Various studies have shown that POVT can lead to sepsis, ovarian infarction or, with extension of the clot into the renal veins and inferior vena cava, ureteral obstruction, hydronephrosis or renal failure . Pulmonary embolism has been a reported complication in 33% of cases with a mortality rate of 4.4% .…”
Section: Complicationsmentioning
confidence: 99%
“…Such pelvic or abdominal venous thrombophlebitis is a rare but serious postpartum complication. This disease is characterized by inflammation or thrombosis of a pelvic or abdominal vein, and patients typically present with fever and abdominal pain within the first postpartum week [ 4 ]. Almost all previous reports have been regarding ovarian vein thrombophlebitis.…”
Section: Discussionmentioning
confidence: 99%